Annual Plan West Bengal 1995-96 Volume II - Planning Commission (Planning Commission, 1995)
Physical Targets and Achievements during the Annual Plan 1994-95 and Proposals for the Annual Plan 1995-96 Financial Outlay : Proposals for TSP Tribal Sub-plan TSP II PHYSICAL TARGETS : PROPOSALS FOR TSP—1995-96 Special Component Plan for Scheduled Castes (SCP-I) Financial Outlay : Proposals for SCP for Scheduled Castes 1995-96 Special Component Plan for Scheduled Castes SCP—II Physical Targets : Proposals for SCP—1995-96
Development and Planning Department Government of West Bengal